CURRENT SUPPLY CHAIN SECURITY TECHNOLOGIES IN CONTEXT (Perner's Contacts, 2012)
The main aim of this paper is to summarize current most important technologies dealing with Supply Chain Security (SCS). In 2009, The World Bank issued useful Supply Chain Security Guide describing worldwide SCS projects and SCS technologies. We focused on SCS technology part of the Guide and prepared comprehensive overview of the SCS technologies that we found to be used in current EU and US SCS-related projects. The projects were selected based on our first-hand experience from January 2012 workshop on SCS organized by EU and held in Brussels. The last chapter of this paper focuses on different approaches of EU and US to SCS research.